Framework for Risk Management in Service Supply Chains - Tuominen, Sami-Janne (My University, 2024)
In this study, a comprehensive framework for supply chain risk management in B2B context was developed. Risk management was examined from the procurement perspective. The theoretical framework is built on previous research, which was mainly based on studies in the manufacturing industry. Based on empirical data, it was not suitable for managing risks in service delivery chains. The empirical data provided a deeper understanding of the nature of service supply chains and demonstrated the need to adapt the theoretical framework to this context. The updated framework based on the empirical data covers risk categorization, risk identification, risk analysis, and risk mitigation, which have been addressed in previous studies as part of comprehensive risk management. The study is a case study focusing on a single company. The empirical data was collected by interviewing seven procurement professionals from the target company. Based on the results, risks were classified into internal, external, and environmental risks. This classification is more suitable for managing risks in service context as it takes into account the nature of services and the importance of different actors in service delivery. The research findings also present a wide range of approaches for risk identification and mitigation, as well as a description of the risk management process, which includes identification, analysis, mitigation, and acceptance. The study also shows that not all services can be treated the same way from a risk management perspective, as there are differences in the risks that affect different services. Despite these differences, there are many similarities in terms of risk management in services, and the risk management process could be applied to all services to some extent. This enables the utilization of the framework as a foundation for comprehensive risk management in service supply chains. The study contributes to the field of risk management, which lacks a comprehensive framework for managing risks in service supply chains.

Tässä tutkimuksessa kehitettiin kokonaisvaltainen viitekehys palvelujen toimitusketjun riskienhallinnalle yritysten välisessä toiminnassa. Tutkimuksessa riskienhallintaa tarkasteltiin hankinnan näkökulmasta. Aiemman tutkimuksen pohjalta rakennettu viitekehys, joka pohjautui pääasiassa valmistavan teollisuuden tutkimuksiin, ei sovellu empiirinen aineisto perusteella soveltunut palveluiden toimitusketjujen riskienhallintaan. Empiirinen aineisto antoi syvempää ymmärrystä palveluiden toimitusketjujen luonteesta ja osoitti tarpeen muokata teorian pohjalta kehitetyn viitekehyksen tähän kontekstiin sopivaksi. Empiirisen aineiston pohjalta päivitetty viitekehys kattaa riskien luokittelun, riskien tunnistamisen, riskianalyysin ja riskien vähentämisen, joita aiemmissa tutkimuksissa on käsitelty osana kokonaisvaltaista riskienhallintaa. Tutkimus on tapaustutkimus, jonka kohteena on yksittäinen yritys. Empiirinen aineisto on kerätty haastattelemalla seitsemää kohdeyrityksen hankinta-ammattilaista. Tuloksien perusteella riskit luokiteltiin sisäisiin, ulkoisiin ja toimintaympäristön aiheuttamiin riskeihin. Tämä luokittelu soveltuu palveluiden riskienhallintaan paremmin sillä se ottaa huomioon palvelujen luonteen ja eri toimijoiden merkityksen palveluiden toteuttamisessa. Tutkimustulos esittää myös laajan valikoiman riskien tunnistamisen ja vähentämisen toimintatapoja sekä kuvaa riskienhallintaprosessin, joka sisältää tunnistamisen, analysoinnin, lieventämisen ja hyväksymisen. Tutkimus osoittaa myös, että kaikkia palveluita ei voida kohdella samalla tavalla riskienhallinnan näkökulmasta, koska palveluiden välillä on eroja vaikuttavien riskien osalta ja niihin sovellettavissa toimintamalleissa. Eroista huolimatta palveluissa on paljon yhtäläisyyksiä riskienhallinnan näkökulmasta, sillä monet riskit vaikuttavat kaikkiin palveluihin ja riskienhallintaprosessia voitaisiin soveltaa kaikkiin palveluihin. Tämä mahdollistaa viitekehyksen hyödyntämisen yrityksissä perustana kokonaisvaltaiselle riskienhallinnalle palvelujen hankintaketjuissa. Tutkimus tukee riskienhallinnan tutkimuskenttää, josta puuttuu kokonaisvaltainen viitekehys palveluiden toimitusketjujen riskienhallinnalle.
Keywords: supply chains; risk management; services; service chains; risk analysis; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development